Diet-related dental wear in archaeological human populations of Chalcolithic and Bronze Age from North-Eastern Romania - Ozana-Maria Petraru; Luminița Bejenaru; Mariana Popovici (Homo, 2022)
Dental macrowear is the non-pathological loss of hard tissues on the occlusal surface of the teeth. In archaeological contexts, the loss of tooth tissues is often correlated with lifestyles, habits, and with the physical properties of the consumed food - including preparation techniques. We report the first semiquantitative and quantitative assessment on dentine exposure of permanent second molars (M2) using the scale scoring technique, image analysis, and regression analysis on human teeth from Chalcolithic and Bronze Age archaeological populations discovered in North-Eastern Romania. We show an increase of dentine exposure percent (PDE) with the age-ranges, but no evidence of wear by sex were observed. In the linear regression analysis, the age and the dentine exposure percent, as variables, were correlated in 31% of the mandibular M2 molars and 49% in the maxillary ones (p < 0.001). Moreover, the multiple regression analysis involving the dentine exposure and the three variables that could influence the dental wear (i.e., age, occlusal area, and period) revealed no differences in dental wear between Chalcolithic and Bronze Age, as well as between different cultures of Bronze Age (i.e., Monteoru Culture and Noua Culture). Therefore, apart from age, occlusal area, and period, there may be other factors including diet and food-processing techniques that could be also considered when discussing the loss of tooth tissues in archaeological populations, especially farmers.